Evaluasi Persampahan di Pulau Barrang Caddi dalam Rangka Mengidentifikasi Isu dan Permasalahan Eksisting Menuju Perbaikan Kualitas Pengelolaan Sampah di Masa Depan - Yashinta Kumala Dewi Sutopo; Muhammad Yamin Jinca; Azizah Putri Abdi; Luvitaliani Luvitaliani; Megawati Viska H. M. (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Island waste is a serious problem. This is because the waste management has not received optimal handling. The study case is located on Barrang Caddi Island, Makassar City which has carried out solid waste operational activities, but there are still several problems in its management. The aim of this research was to evaluate the waste management on Barrang Caddi Island in order to improve the quality of the system in the future. This research was conducted from September 2019 to January 2020 (4 months). The data obtained are primary data (compartment, sorting, collection, processing, transportation, and final disposal) and secondary (recapitulation of waste sales and population). The analysis used is a qualitative descriptive analysis. The results showed that there is a problem, namely a communal trash container is needed for public places on the island, it requires community participation in sorting waste and community concern in protecting the environment, and government support is needed in providing waste facilities such as waste boat transportation, parking lots for motorbikes to collect waste, and repairs incinerator.